Design of energy efficient four finger robotic hand - Bhivraj Suthar (Institute of Advanced Engineering and Science, 2016)
Future would be the world of robotics. Human arm is the best serial manipulator in the world. End part of manipulator is known as End effector or hand. At the end of serial manipulator we always put gripper just like our hand. Today many mechanisms have been proposed for robotic hand. We proposed a novel mechanical design and we used one motor to operate the gripper mechanism and it consumes less electrical power than other gripper. For energy efficient robot we have to reduce the number of motors and have to look in the mechanical design. In this paper we targeted to make gripper more energy efficient. We used only one motor to operate four fingers symmetrically. Our proposed model has four fingers, each are placed orthogonally to each other. In market, other manufactures use single motor for motion of each finger. Each motor has its own power consumption capacity to manipulate the load on finger. We replaced all four motors with single motor by Geneva mechanism. So electrical power consumption reduced by 1/4th. Energy conservation point of view it is energy efficient system. This paper presents a methodology that has been applied for a design mechanism for energy efficient robotic hand with four fingers. Wide applications of gripper are in automobile industries. Automobile companies are used gripers and serial manipulators in plenty